Alveolar epithelial and vascular CXCR2 mediates transcytosis of CXCL1 in inflamed lungs - Katharina Thomas; Jan Rossaint; Nadine Ludwig; Sina Mersmann; Niklas Kötting; Julia Grenzheuser; Lena Schemmelmann; Marina Oguama; Andreas Margraf; Helena Block; Katharina Henke; Katharina Hellenthal; et al. (Nature Communications)
Abstract Pulmonary infections are characterized by neutrophil recruitment into the lung driven by chemokine ligands of CXCR2, which is expressed on neutrophils, but also present in non-hematopoietic lung cells, in which its role remains unclear. We hypothesize that CXCR2 in epithelial and endothelial cells contributes to neutrophil recruitment into the lung by modifying the availability of its cognate chemokines in lung alveoli. Using conditional endothelial and epithelial CXCR2 knockout mice, we demonstrate that selective CXCR2 deletion in either compartment impairs neutrophil recruitment into the lung during bacterial pneumonia and reduces bacterial clearance. We show that CXCR2 ablation in epithelial and endothelial cells compromises respective trans-epithelial and trans-endothelial transcytosis of alveolar CXCL1. Mechanistically, CXCR2-mediated CXCL1 endothelial and epithelial cell transcytosis requires the function of Bruton’s tyrosine kinase in these cells. In conclusion, CXCR2 plays an important role in alveolar epithelial and endothelial cells, where it mediates cognate chemokine transcytosis, thus actively supporting their activities in neutrophil recruitment to the infected lungs.